Quantitative comparison of ultracentrifuged and diluted single walled nanotube - COLEMAN, JONATHAN (My University, 2009)
We have carried out a quantitative comparison of the dispersion quality for ultracentrifuged and diluted surfactant-stabilised single walled nanotube dispersions. We have characterised these dispersions at a set concentration of not, vert, similar30 ?g.mL-1 by absorption and photoluminescence spectroscopy as well as by statistical atomic force microscopy. Both the ultracentrifuged and the diluted samples contained significant quantities of bundles as well as individual nanotubes. The ultracentrifuged sample contained not, vert, similar 4 times more individualised SWNTs than the diluted sample with partial concentrations of individual nanotubes of 4.8 and 1.1 ?g.mL-1 respectively.
ACCEPTED
Keywords: Physics; Nanoscience & Materials